THE ROLE OF RADIOLOGIC IMAGING IN IRRITABLE BOWEL SYNDROME (IBS): A SYSTEMATIC REVIEW - Nuswantoro, Yoga; Anggraini, Efa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: The role of radiologic imaging in the investigation of irritable bowel syndrome (IBS) remains a subject of debate and there is some evidence, from recent studies of utilization of imaging in IBS, which focused on associated costs and radiation exposure, that imaging is being used relatively widely in these patients. The aim: This study aims to show the role of radiologic imaging in irritable bowel syndrome (IBS). Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 112 articles, whereas the results of our search on SagePub brought up 179 articles. The results of the search conducted for the last year of 2013 yielded a total 84 articles for PubMed and 91 articles for SagePub. The result from title screening, a total 18 articles for PubMed and 25 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: In patients presenting with IBS symptoms and alarm features, radiologic testing may be used to exclude an alternative diagnosis and the imaging modality should be chosen based on the most likely alternative diagnosis.